"Any press is good press?" Rebel political wings, media freedom, and terrorism in civil wars. Issue 1 (2nd January 2019) - Keels, Eric; Kinney, Justin
ABSTRACT: As part of a recent effort to bridge the studies of terrorism and civil war, new research has begun to emerge on the use of terrorism by rebel groups as a strategy of war. Building on these findings, we examine the role of affiliated political wings in shaping the use of terrorism by rebel groups during civil wars. We contend that the presence of an affiliated political wing during the civil war should increase the use of terrorism by rebel groups only in countries where there are relatively few restrictions on the freedom of the press. As political wings are often designed to engage with the civilian population through the dissemination of information, these apparatuses are in a key position to frame the use of terrorism as part of the rebel's broader war effort. To test this proposition, we examine the use of terrorism by all rebel groups from 1970 to 2011. The results from the analysis provide strong support for our argument that political wings increase the use of terrorism by rebel groups only when the press is allowed to independently cover terrorist attacks.